2009
DOI: 10.1074/jbc.m109.045021
|View full text |Cite
|
Sign up to set email alerts
|

Migfilin Interacts with Src and Contributes to Cell-Matrix Adhesion-mediated Survival Signaling

Abstract: Integrin-mediated cell-extracellular matrix (ECM) adhesion is essential for protection of epithelial cells against apoptosis, but the underlying mechanism is incompletely understood. Here we show that migfilin, an integrin-proximal adaptor protein, interacts with Src and contributes to cell-ECM-mediated survival signaling. Loss of cell-ECM adhesion markedly reduces the migfilin level in untransformed epithelial cells and concomitantly induces apoptosis. Overexpression of migfilin substantially desensitizes cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
0
29
1
Order By: Relevance
“…FBLP-1 possesses multiple protein binding activities but no catalytic activities (15,(21)(22)27). Thus, the strong dependence of healthy bone on FBLP-1 likely reflects a critical role for one or multiple FBLP-1-mediated interactions in this organ that is undergoing continuous cycles of remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FBLP-1 possesses multiple protein binding activities but no catalytic activities (15,(21)(22)27). Thus, the strong dependence of healthy bone on FBLP-1 likely reflects a critical role for one or multiple FBLP-1-mediated interactions in this organ that is undergoing continuous cycles of remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we have found that FBLP-1 interacts with several important actin cytoskeletal and signaling proteins including filamin (15,21,22). Although in vitro studies using cultured cells and/or purified proteins have pointed to a role of FBLP-1 in regulation of cell-ECM adhesion, migration, cytoskeletal organization, and intracellular signaling (15,(21)(22)(23)(24)(25)(26)(27)(28)(29), the functions of FBLP-1 in tissues and organs were not known. To address this question, we have inactivated FBLIM1 (the gene encoding FBLP-1) in mice and determined the functional consequences.…”
mentioning
confidence: 99%
“…Furthermore, migfilin is also present in the nucleus, where it might co-activate transcription factors including Nkx2.5 (Akazawa et al, 2004), whose activity is essential for heart morphogenesis. Finally, migfilin has also been shown to bind to c-Src, which promotes cell survival (Zhao et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Numerous kinase/phosphatase signaling molecules are known to be involved in anoikis as central regulators, such as Ras (12), Akt and raf (13). Other reports have also confirmed that cell cytoskeletal rearrangement is critical for the cells to survive anoikis resistance (14,15). Moreover, this process is especially associated with cadherin family members, which are the key elements in the complex network of survival signaling (16).…”
Section: Introductionmentioning
confidence: 87%